Devices that Assist MND Patients - L, Divyashree; S, Nidhi; S, Ankitha C; Bhandari, Keshav Kumar; C, Karthik N (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2021)
Several researches have been carried out over the past years to assist the patients suffering from Motor Neuron Disease (MND) to communicate effectively. Though many interpretations exist, they are extremely outrageous and torpid in user response. This survey paper presents designing a wireless handheld device to assist the MND patients to communicate using series of blink.